Transitions in sense of coherence among middle-aged women raising adolescents before and during the COVID-19 pandemic - Omiya, Tomoko; Sankai, Tomoko; Miyazaki, Akari; Abe, Yoshiki; Deguchi, Naoko Kumada (Frontiers in Psychology, 2023)
Objective A longitudinal study was conducted among Japanese women raising adolescents to determine how the COVID-19 pandemic has affected their sense of coherence (SOC) and to provide suggestions for supporting them. Methods The SOC scores of 138 pairs of middle-aged women and their children (junior high school students) were compared at two time points: 2019 (before the pandemic, T1) and 2020 (during the pandemic, T2). Results Overall, the women’s SOC did not change, whereas the adolescents’ SOC increased. In contrast, 44% of the women’s SOC scores decreased during the pandemic; no differences were detected between the SOC maintenance and increase group (G1) and the SOC decrease group (G2) in mental health, subjective physical health, social capital, and job status, and the child variables were not related. Multiple regression analysis of G1 and G2 with SOC at T2 as the dependent variable showed that for G2, at T1, having good mental and physical health conditions, a rich social capital, and having a job were positively associated with SOC during the pandemic. Conclusion Middle-aged Japanese women, who often work as informal workers, are easily laid off and are involved in care work. Thus, the change in their socioeconomic status due to the pandemic may have been severe. Given the long-term social impact of the pandemic, it is necessary to consider support for women, including economic and social support such as employment and building human connections.